2000
DOI: 10.1007/s002080000116
|View full text |Cite
|
Sign up to set email alerts
|

Fuchsian groups, automorphic functions and Schwarzians

Abstract: In this paper, a close connection is established between the geometry of certain genus zero Fuchsian groups and the analytic properties of the automorphic forms obtained by applying a certain differential operator to the Hauptmoduls of the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 9 publications
1
48
0
Order By: Relevance
“…This was used by Poincaré in his 1882 paper Mémoire sur les fonctions fuchsiennes [12]. It also appears in [5,8,10,11]. We give some properties of the Schwarz derivative (see [9]).…”
Section: Definition and Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This was used by Poincaré in his 1882 paper Mémoire sur les fonctions fuchsiennes [12]. It also appears in [5,8,10,11]. We give some properties of the Schwarz derivative (see [9]).…”
Section: Definition and Propertiesmentioning
confidence: 99%
“…In [10], it was shown that the Schwarz derivative can have an important role in the theory of modular forms as well. The following proposition is an example.…”
Section: Schwarz Derivative Of Modular Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, explicit instances of all of these objects in the case of higher genera would enable one to construct nice applications wherever algebraic functions and Riemann surfaces appear. Such topics include algebraic-geometric integration, conformal field theories [1], integrable quantum/classical dynamical systems and nonlinear pde's, equations of Picard-Fuchs [10,14], second order linear ordinary differential equations (ode's) of Fuchsian type [21], number theory, "Monstrous Moonshine" [13], and many others. Yet another and deep application of uniformization originated in works of Takhtajan and collaborators in the late 1980's and for further applications of the general uniformization theory see work [1] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…This study was motivated by previous work in collaboration with John McKay, [2,3], in which we studied the properties of Hauptmoduls originating from Moonshine under the action of the Schwarzian derivative.…”
Section: Introductionmentioning
confidence: 99%